Petrogenesis and tectonic setting of the Middle Devonian Beitashan Formation volcanic rocks in the northern East Junggar, NW China: Insights from geochemistry, zircon U–Pb dating, and Hf isotopes. (2nd December 2019) - Xu, Qian; Li, Yongjun; Yang, Gaoxue; Ning, Wentao; Tong, Lili; Duan, Fenghao; Wu, Le; Ren, Pengfei
Abstract : The Devonian volcanic rocks are widely distributed in the East Junggar (Xinjiang, NW China), preserving important magmatic records for investigating Palaeozoic tectonic evolution. The Beitashan Formation is mainly composed of pyroclastic rocks and sedimentary rocks in the lower section and intermediate–basic volcanic lava and pyroclastic rocks in the upper section. In this paper, we present geochronological, geochemical, and in situ Lu–Hf isotopic data for Beitashan Formation volcanic rocks from the East Junggar. Zircon U–Pb analyses from a basalt sample by laser ablation inductively coupled plasma mass spectrometry yielded a weighted mean age of 387.8 ± 4.5 Ma, indicating that it was generated in the Middle Devonian. The basic–intermediate volcanic rocks are tholeiitic to calc‐alkalic and are characterized by MgO (2.29–5.91 wt.%), low TiO2 (0.75–1.36 wt.%), and relatively high Al2 O3 (15.82–16.73 wt.%). Furthermore, they display enrichment in light rare‐earth elements and large‐ion lithophile elements (such as Ba and Sr) and depletion in Nb, Ta, and Ti, along with slightly positive Eu anomalies (δEu = 0.83–1.15) and Ce anomalies (δCe = 1.00–1.11). In addition, in situ zircon Hf isotopic analyses from basalt samples show εHf ( t ) values ranging from +4.33 to +15.2, indicating a depleted mantle source with minor crustal contamination. They also show relatively low Nb/Zr (0.04–0.06), Th/Yb (0.67–3.83), and Ba/La (6.79–67.53) and high Ce/Th (7.71–18.94), Ba/Rb (21.39–294.28), and Ba/Th (31.42–486.58). The geochemical data suggest these rocks were likely derived from 10% to 30% partial melting of a garnet‐rich with minor spinel‐bearing Iherzolite depleted mantle metasomatized by slab‐derived fluids, with crustal contamination. Combined with the geological setting and previous studies, we suggest that the northern East Junggar was in a northward‐subducted island‐arc setting in the Devonian.